2012
DOI: 10.1016/j.outlook.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research nursing: A critical resource in the national research enterprise

Abstract: Translational clinical research has emerged as an important priority for the national research enterprise, with a clearly stated mandate to deliver prevention strategies, treatments and cures based on scientific innovations faster to the public. Within this national effort, a lack of consensus persists concerning the need for clinical nurses with expertise and specialized training in study implementation and the delivery of care to research participants. This paper reviews efforts to define and document the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 71 publications
1
74
0
4
Order By: Relevance
“…In a setting where there is an increasing trend in non-nurse study positions; it is important for nursing to advocate for both study participants and the study protocol by exploring a means for comparing outcomes based on staffing and defining nurse-sensitive indicators. 15 This is a small pilot study; therefore, several limitations are inherent in this study and results should be carefully interpreted. One factor that could lead to a misinterpretation of the data was the heterogeneity present among several aspects of the data.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a setting where there is an increasing trend in non-nurse study positions; it is important for nursing to advocate for both study participants and the study protocol by exploring a means for comparing outcomes based on staffing and defining nurse-sensitive indicators. 15 This is a small pilot study; therefore, several limitations are inherent in this study and results should be carefully interpreted. One factor that could lead to a misinterpretation of the data was the heterogeneity present among several aspects of the data.…”
Section: Discussionmentioning
confidence: 95%
“…[15][16][17] The American Nurses Association (ANA) and the International Association of Clinical Research Nurses have copublished Scopes and Standards of Clinical Research Nurses. 18 ANA formally recognized clinical research nursing as a professional nursing specialty.…”
Section: Introductionmentioning
confidence: 99%
“…They also add that nurses who provide health care or coordinate studies can, according to their expertise, improve the efficiency of investigation, safety of participants and quality of data (8,9) . This was observed in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse demonstrate their knowledge to anticipate risk situations and include in the project, in detail, the care needed to assure the assistance to participants in all phases of the research to which they are associated with (8) . In their academic background, the content offered to nurses about nursing theories that give support to care focused on human needs (as the one proposed by Horta), and the application of the nursing process can contribute to risk analysis and to plan specific health care.…”
Section: Discussionmentioning
confidence: 99%
“…Mueller (2001) noted that the roles of nurses working in clinical research have evolved into independent roles following decades of task delegation by physician investigators (PIs) and that those independent roles constitute a unique specialization in nursing. Hastings, Fisher, and McCabe (2012) observed that nurses working in clinical research have made contributions to the research findings that support evidence-based practice through the key roles they perform in coordinating and managing research involving human subjects.…”
Section: Introductionmentioning
confidence: 99%